(untitled) (Castilla. Estudios de Literatura, 2016)
Was José Joaquín de Mora a Protestant? Perhaps due to the similarities with Blanco White’s situation, those who believe in Mora’s conversion maintain that Mora abandoned Catholicism during his first exile inLondon. With Mora’s own texts as backing evidence, this article states that Mora’s conversion did not take place till the 1850’s, when Mora was already 70 years old. It is only then that enough signs, such as his likely authorship of an anti-Catholic tract published anonymously in 1855 or his presence in Protestant hymnals, lead us to consider Mora’s conversion as a reality.